2018
DOI: 10.1016/j.bjid.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human cysticercosis in Jataí, Goiás state, Brazil

Abstract: The Taenia solium cysticercosis affects millions of people worldwide and is considered a public health problem, especially in developing countries. The diagnosis of neurocysticercosis is complex and involves the analysis of epidemiological, clinical, neuroimaging, and immunological host data. Neurocysticercosis is endemic in Brazil, and is related to the cause of death mainly in the Southeast, South, and Central-West regions. The objective of this study was to determine the seroprevalence of cysticercosis in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…Our research team previously reported a prevalence of 13.8% for CC in serum samples from individuals in clinical laboratories, including children (8.2%), adults (75.3%), and older adults (16.5%) of both sexes living in Jataí ( 11 ). In Catalão City, state of Goiás, a seroprevalence of 11.3% for CC was significantly associated with the absence of an urban sewage network ( 22 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our research team previously reported a prevalence of 13.8% for CC in serum samples from individuals in clinical laboratories, including children (8.2%), adults (75.3%), and older adults (16.5%) of both sexes living in Jataí ( 11 ). In Catalão City, state of Goiás, a seroprevalence of 11.3% for CC was significantly associated with the absence of an urban sewage network ( 22 ).…”
Section: Discussionmentioning
confidence: 98%
“…In the southern region, CC seroprevalence was 3.4% in Lages-SC ( 10 ). In the Midwest, a study demonstrated a seroprevalence of 13.8% for CC in adults living in the municipality of Jataí-GO ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Demais fatores também contribuem para a maior ou menor ocorrência da doença, com destaque para o consumo de carne vindo de abates clandestinos sem a inspeção sanitária e que possam estar contaminadas, podendo os números de humanos infectados serem consideravelmente maiores que os relatados na literatura (Pereira et al, 2006). Relatos atuais sobre a ocorrência de cisticercose no Brasil são escassos, não sendo possível determinar com exatidão por regiões a real prevalência, segundo Guarda et al (2018), alguns dos municípios brasileiros chegam a apresentar um número preocupante e grave de até 13,8% de soroprevalência.…”
Section: Anounclassified
“…A cisticercose é endêmica em vários países da América Latina, África Subsaariana e Ásia, incluindo a Índia, a maior parte do sudeste da Ásia e a China (CORAL-ALMEIDA et al, 2015;EDIA-ASUKE et al, 2015;THOMAS et al, 2016;GUARDA;COSTA-CRUZ;BARCELOS, 2018;WHO, 2015;OPENSHAW et al, 2018). Essa doença alcança milhões de pessoas em todo o mundo, sobretudo os países em desenvolvimento e ainda alguns desenvolvidos, onde a imigração ainda é um grande fator de risco para acometimentos (MAGALHÃES et al, 2017;WHO, 2015).…”
Section: Epidemiologiaunclassified